UMAR IBN KHATTAB, AN EPITOME OF SERVANT LEADERSHIP: A SUSTAINABLE LESSON FOR CONTEMPORARY LEADERS - Ahamad Faosiy, Ogunbado; Yusuf Sani, Abu bakar; Mpawenimana, Abdallah Saidi (Advance Scientific Research, 2020)
Servant Leadership is believed to have been a new theory coined and inserted into the field of leadership and management by an American Scholar, Robert Greenleaf in early 1970s. Since then, it has been one of the important types of leadership that attract the interest of the Scholars or Researchers. Therefore, the paper intends to portray an icon and epitome of such leadership stylefrom Islamic perspective, ‘Umar ibn Khattab (r.a), the second Caliph in Islam. It presents the historical background of the icon. It also discusses the definition and origin of the theory. The paper also enumerates evidences of emulation of the icon from authentic literature. Likewise, it portraysthe servant leadership characteristics as it can be seen in ‘Umar’s personality (r.a). In an attempt to dig into the root ofthe theory, the paper looks into the Chinese, Christianity and Western perspectives of the style. The study contains no numericalor statistical value in achieving its aims and objectives, that is to say, purely qualitative research methodology is employed. The study re-emphasizes that the theory is one of the theories or styles which have been enshrined in Islam since 14 century ago. It also depicts that ‘Umar ibn Khattab (r.a) was an important figure to be emulated in actualizing the theory. It is anticipated that sustainability of a good governance and management in any given community or organization will be achieved by putting the characteristics into practice. Furthermore, it is expected that many contemporary leadership dilemmas will be overcome, if the contemporary leaders follow the Caliph’s step.